The Importance of the Competitive Environment in the Development of Enterprise Strategy (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The main factors affecting the level of competition in the service network in the circumstances business structures competitiveness national economy and necessity prove economy host of subjects innovative activity allows to increase.